2001
DOI: 10.1176/appi.ajp.158.10.1706
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Motivational Interviewing, Cognitive Behavior Therapy, and Family Intervention for Patients With Comorbid Schizophrenia and Substance Use Disorders

Abstract: These findings demonstrate the effectiveness of a program of routine care integrated with motivational interviewing, cognitive behavior therapy, and family intervention over routine psychiatric care alone for patients with comorbid schizophrenia and alcohol or drug abuse or dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
294
5
24

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 455 publications
(331 citation statements)
references
References 27 publications
8
294
5
24
Order By: Relevance
“…There is growing agreement that an integrated treatment approach is a more appropriate model [9][10][11][12][13][14] than treatments that address each disorder separately. Previous studies have also shown strong preference among women with a dual diagnosis for integrated treatment.…”
Section: Integrated Treatment Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing agreement that an integrated treatment approach is a more appropriate model [9][10][11][12][13][14] than treatments that address each disorder separately. Previous studies have also shown strong preference among women with a dual diagnosis for integrated treatment.…”
Section: Integrated Treatment Approachmentioning
confidence: 99%
“…Previous studies have also shown strong preference among women with a dual diagnosis for integrated treatment. 13,15 Some components for successful integrated treatment models include stages of change components, motivational interviewing, and cognitive-behavioral interventions, 11,12,16,17 plus screening for trauma and health problems as well as an approach that builds on safety and empowerment in the community. 18 For women with a substance abuse or dependence disorder, especially PTSD, it has been suggested that comprehensive treatments should address substance use and directly intervene with PTSD symptoms and quality of life concerns such as vocational issues and social support.…”
Section: Integrated Treatment Approachmentioning
confidence: 99%
“…Most trials did not achieve full blindness although many studies attempted to single blind at least some measurements (Barrowclough 2001;Falloon 1981;Goldstein 1978;Leavey 2004;Merinder 1999;Vaughan 1992;Zhang 1994). …”
Section: Assessment Of Reporting Biasesmentioning
confidence: 99%
“…Where family members or carers are present, family interventions have also been viewed as important. Evaluations of this type of approach have shown significant benefits over treatment as usual (case management and anti-psychotic medication for mental health and substance use services) for a 9 month treatment with benefits at the end of the treatment period and at follow-up points (Barrowclough et al, 2001;Haddock et al, 2003).…”
Section: Substance Usementioning
confidence: 99%